Activation of angiotensin-converting enzyme 2 ameliorates metabolic syndrome-induced renal damage in rats by renal TLR4 and nuclear transcription factor κB downregulation - El-Domiaty, Heba F.; Sweed, Eman; Kora, Mona A.; Zaki, Nader G.; Khodir, Suzan A. (Frontiers in Medicine, 2022)
Background: Metabolic syndrome (MetS) is an independent risk factor for chronic kidney disease through many mechanisms, including activation of the renin–angiotensin system. The deleterious effects of angiotensin II (Ang II) can be counterbalanced by angiotensin-converting enzyme 2 (ACE2). Diminazene aceturate (DIZE), an anti-trypanosomal drug, can activate ACE2. Objective: This study aimed to investigate the possible reno-protective effects of DIZE in MetS rats with elucidation of related mechanisms. Materials and methods: Thirty adult male Wistar albino rats were divided equally into control, MetS, and MetS + DIZE groups. Body weight, systolic blood pressure (SBP), and urinary albumin levels were measured. Serum levels of fasting blood glucose (FBG), insulin, uric acid, lipid profile, urea, and creatinine were measured. Homeostasis Model Assessment Index (HOMA-IR) was estimated. Subsequently, levels of Ang II, malondialdehyde (MDA), reduced glutathione (GSH), and tumor necrosis factor-α (TNF-α) were measured with histopathological and immunohistochemical assessment of TLR4 and NF-κB in renal tissues. Results: MetS caused dyslipidemia with significant increases in body weight, SBP, FBG, serum insulin, HOMA-IR, uric acid, urea, creatinine, urinary albumin, and renal levels of Ang II, MDA, and TNF-α, whereas renal GSH was significantly decreased. Renal TLR4 and NF-κB immunoreactivity in MetS rats was upregulated. DIZE supplementation of MetS rats induced significant improvements in renal function parameters; this could be explained by the ability of DIZE to decrease renal Ang II levels with downregulation of renal TLR4 and NF-κB expression. Conclusion: DIZE exerts a reno-protective effect in MetS, mainly by downregulating renal TLR4 and NF-κB levels.